C−H Coupling Reactions Directed by Sulfoxides: Teaching an Old Functional Group New Tricks. Issue 34 (13th July 2016) - Pulis, Alexander P.; Procter, David J.
Abstract: Sulfoxides are classical functional groups for directing the stoichiometric metalation and functionalization of C−H bonds. In recent times, sulfoxides have been given a new lease on life owing to the development of modern synthetic methods that have arisen because of their unique reactivity. They have recently been used in catalytic C−H activation proceeding via coordination of an internal sulfoxide to a metal or through the action of an external sulfoxide ligand. Furthermore, sulfoxides are able to capture nucleophiles and electrophiles to give sulfonium salts, which subsequently enable the formation of C−C bonds at the expense of C−H bonds. This Review summarizes a renaissance period in the application of sulfoxides arising from their versatility in directing C−H functionalization. Abstract : Classical sulfoxide directing groups have been given a new lease on life because of their unique ability to direct a variety of C−H couplings to form important C−C bonds. Sulfoxide direction operates through internal coordination to a metal (directing groups), through external coordination (ligands), or via sulfoxide capture of nucleophilic or electrophilic coupling partners (sulfonium‐directed).